Pembelajaran Jarak Jauh di Era Pandemi Covid 19: Studi Terhadap Pembelajaran PAI di Kelas VIII SMP Islam Prestasi Al Mubtadi-Ien - Muhamad Mujib; Dimas Ahmad Rizal (Lembaga Sosial Rumah Indonesia, 2022)
This research is a descriptive qualitative study, which explains a recent phenomenon through open interviews to examine and understand the events that occurred during the implementation of Distance Learning (PJJ) at Al Mubtadi-Ien Islamic Junior High School, Bantul during the Covid 19 pandemic. The results showed that the selection of the lecture method as an effective learning method to be applied in distance learning in class VIII Islamic Junior High School Prestasi Al Mubtadi-Ien. Several stages that must be considered in the use of the lecture method are conveying the learning objectives, adjusting the accuracy of the method, managing the attention and condition of students, presenting material, providing conclusions, and conducting evaluations. The use of the lecture method in distance learning of Islamic Religious Education at SMP IP Al Mubtadi-Ien, especially in class VIII emphasizes students' understanding of the material presented by the teacher, with the help of additional platforms to optimize the teaching and learning process